When did the future Antiochos iv arrive in Athens? - Scolnic, B. (Hesperia, 2014)
The mention of an Antiochos in an Athenian inscription, I 7453, which dates to 178/7 b.c., has led scholars to accept that the future Antiochos IV lived in Athens from 178 to 175, and was not just present in the city in 175, as a statement by Appian seems to indicate. A reevaluation of the evidence calls into question both this extended sojourn and the identification of the Antiochos in the inscription, inviting us to reconsider the circumstances and the chronology of events surrounding the accession of Antiochos IV. © The American School of Classical Studies at Athens.
1 citations (Crossref) [2023-10-31]
Keywords: dept.jst

Heliodorus and the Assassination of Seleucus IV according to Dan 11:20 and 2 Macc 3 - Scolnic, B. (Journal of Ancient Judaism, 2016)
The impetus for the assassination of Seleucus IV in 175 B. C. E. is commonly associated with his robbing the temples and oppressing the peoples of the Seleucid kingdom in order to pay tribute to Rome according to the Treaty of Apamea. Reconsideration of the relevant evidence – especially Dan 11:20 and 2 Macc 3, with attention to a passage from Appian, inscriptions from Delos, the Heliodorus stele and the Ptolemaios dossier – suggests another explanation for these events. If Seleucus robbed the temples to finance his “royal splendor,” it is possible that Heliodorus and others tasked with taxing the kingdom may have objected to his controversial policies and taken action against him because of them. © 2016 [2017] Vandenhoeck & Ruprecht GmbH & Co. KG, Göttingen
0 citations (Crossref) [2023-10-31]
Keywords: dept.jst

Is Daniel 11:1-19 based on a ptolemaic narrative? - Scolnic, Benjamin (Journal for The Study of Judaism, 2014)
Daniel 11 is considered an exceptional Biblical text because of its interest in and accuracy about historical and political events in the Hellenistic world. A recent theory suggests that the author was a former Seleucid scribe; another theory posits the use of a Ptolemaic propaganda document. The approach here will be inductive, reading out from the text to adduce evidence that the author of Daniel 11 either used or reflected the attitudes of Ptolemaic narrative, not necessarily because he was pro-Ptolemaic but because it suited his anti-Antiochene purpose. © Koninklijke Brill NV, Leiden, The Netherlands.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/035-586-778-649-478 tex.type: [object Object]
Keywords: Bible; Daniel; Maccabean; Source criticism; dept.jst

Antiochus IV as the scorned prince in dan 11:21 - Scolnic, Benjamin (Vetus Testamentum, 2012)
While most English translations render nbzh in Dan 11:21 as "contemptible, vile, despicable," closer examination will demonstrate that this Biblical Hebrew word should be translated as "spurned, scorned, rejected." Once one understands Dan 11:21 accordingly, other ancient sources can be brought to show that this verse states, in its own thinly-veiled code, that before his rise to power, Antiochus IV, son of the late king Antiochus III and brother of the current king Seleucus IV, had been scorned and had not been given appropriate royal honors. This verse should be seen as another element in the evaluation of Dan 11 as an accurate and important historical source for the events surrounding the rise and rule of Antiochus IV. © 2012 by Koninklijke Brill N.V., Leiden, The Netherlands.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/003-577-169-045-737 tex.type: [object Object]
Keywords: Daniel; Hebrew Bible; Old Testament; dept.jst; translation